Development of Economic Analysis: Predictive Analytics, ESG Analytics, Analysis of Transformation Processes at the Meso- and Micro-Levels - V. G. Kogdenko (Учёт. Анализ. Аудит)
This article explores the key areas shaping the future of economic analysis. The evolving Russian economy, marked by digital transformation, shifting goals, and a move away from resource-based to technology-driven models, has given rise to three critical analytical frontiers. The first is predictive analytics. This approach encompasses strategic assessments, revenue forecasting, investment modeling, dividend analysis, external capital needs, profit simulations, stress testing, and fundamental cost calculations. It evaluates forecast accuracy to guide informed decision-making. The second is ESG analysis. This evaluates a company’s impact on economic, social, and environmental factors. It measures capital value, assesses social and environmental impacts, and analyzes value distribution. This methodology determines the company’s development path and ESG maturity stage, promoting sustainable growth. The third is transformational process analysis. At the meso level, it identifies high-value activities driving economic growth. Prioritizing these activities shapes a new economic model. At the micro level, it evaluates transformation prerequisites, innovation, investments, and success metrics like added value, productivity, and localization. This research is valuable for investors, creditors, and government agencies shaping industrial policy. It provides insights into economic trends and strategies for sustainable growth.